Measuring the immeasurable by proposing a CSR index - Younas, Afshan (Edelweiss Applied Science and Technology, 2024)
Corporate social responsibility (CSR) is an admirable notion that should be followed by modern business. There has been an incredible amount of scholarly literature on developed economies of CSR activities over the years. However, the literature lacks the emerging economies' perspectives on how to measure CSR activities and what benefits developing countries’ businesses can reap from being a socially responsible corporate citizen such as CSR-oriented business. The study proposes a conceptual framework that aims to explore the measurement of CSR performance by proposing a CSR index relevant to Oman’s society. The proposed CSR index suggests following a content analysis approach which covers six dimensions of CSR in general. The paper offers a novel contribution to the literature by highlighting the CSR measurement approach referring to Oman’s economy which is aligned with Oman's 2040 vision, Oman's code of corporate governance, and UN Sustainability Development Goals (SDGs). The proposed CSR index highlights the benefits that are associated with the disclosure and measurement of CSR activities. The proposed conceptual CSR framework in this study offers a unique contribution to the body of knowledge and practical implications in Oman. Oman is the first country in the GCC (Gulf Cooperation Council) countries to develop corporate governance principles but still, the implementation is weak. Mandatory corporate social responsibility disclosure measurement is one of the aims of this research. Thus, the proposed CSR index is an ideal evaluative tool for Omani businesses’ performance in the CSR domain.